Cyclosporin A retention enemas in refractory distal ulcerative colitis and 'pouchitis'. - Winter, T; Dalton, H; Merrett, M; Campbell, A; Jewell, D (1993)
The aim of this study was to evaluate the use of cyclosporin enemas in patients with distal ulcerative colitis and 'pouchitis' resistant to all conventional medical therapy. In an trial 12 patients with distal ulcerative colitis unresponsive to treatment with topical and oral corticosteroids, 5-aminosalicylic acid, and oral immunosuppressive therapy together with 1 patient with 'pouchitis' unresponsive to repeated courses of antibiotics, topical corticosteroids, and oral mesalazine received 250 mg cyclosporin administered daily as a retention enema. Changes in symptoms and the sigmoidoscopic/histologic appearances of the rectal mucosa were assessed at monthly intervals. Seven of 12 patients with ulcerative colitis improved. There was a strong correlation between clinical and histologic improvement (p < 0.005). Four of 12 patients showed no response. Three of these required colectomy, two of whom had more extensive disease than had previously been documented. The patient with pouchitis showed improvement in symptoms and 'pouchoscopy' appearance but not in histologic score. Cyclosporin blood concentrations were very low and side effects negligible. Cyclosporin A retention enemas are safe and may be useful in the treatment of severe refractory distal ulcerative colitis. A controlled trial would now seem warranted.